Brief Report: Lower Socioeconomic Status Associates With Greater Systemic and Arterial Inflammation in HIV. (1st May 2021) - Zhang, Lili; Abohashem, Shady; Osborne, Michael T.; Naddaf, Nicki; Park, Rebecca; Moore, Kelvin; Patrich, Tomas; Deeks, Steven G.; Hsue, Priscilla Y.; Tawakol, Ahmed A.
Abstract : Objectives: In the general population, the lower socioeconomic status (SES) associates with greater systemic and arterial inflammation and a greater risk of cardiovascular disease. Because arterial inflammation is heightened in individuals living with HIV, we tested the hypothesis that SES associates with arterial inflammation in this population. Settings: Prospective cohort study. Methods: Men living with HIV were recruited. Arterial inflammation and leukopoietic activity (ie, bone marrow activity) were measured using 18 F-fluorodeoxyglucose positron emission tomography/computed tomography. Zip code-level SES measures were derived from the US Census Bureau. Linear regression and mediation analyses were used to assess associations between SES, arterial inflammation, leukopoietic activity, C-reactive protein (CRP), and interleukin-6. Results: Thirty-nine virologically suppressed men living with HIV were studied (mean ± SD age 50.5 ± 11.1 years). The median CD4 count was 663 cells/mm 3 (interquartile range: 399–922); 82% were receiving antiretroviral therapies. Local median income inversely associated with arterial inflammation [standardized β (95% confidence interval): −0.42 (−0.76 to −0.08)] after adjusting for age, Framingham risk score, statin use, antiretroviral use, and nadir CD4 count. The high-school graduation rate independently associated with arterial inflammation [−0.45 (−0.78 to −0.12)] and CRP [−0.49 (−0.86 to −0.012)]. Mediation analysis demonstrated the impact of SES on arterial inflammation was partially mediated by heightened circulating inflammatory levels: ↓SES (as high school graduation rate) →↑CRP →↑arterial inflammation accounting for 44% of the total effect ( P < 0.05). Conclusion: In individuals living with HIV, lower SES independently associated with higher leukopoietic activity, circulating markers of inflammation, and arterial inflammation. Furthermore, the link between SES and arterial inflammation was mediated by increased systemic inflammation. Abstract : Supplemental Digital Content is Available in the Text.